Team Motivation and Interaction: A Multilevel, Self-Determination Theory Approach - Agate, Daniel Douglas (Curtin University, 2025)
This dissertation empirically evaluated self-determination theory as a framework for understanding the process-based nature of motivation and effectiveness in work teams. Specifically, psychological need support/thwarting was used to operationalise team interactions; motivation was defined multidimensionally, and within-team differences were investigated as substantively significant; and contributions of these variables on team effectiveness were examined. Evidence across the included manuscripts supports the research model and the integration of SDT with research on teams to catalyse future investigation.